2022
DOI: 10.1590/1678-9865202235e210098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kefir consumption on the lipid profile for individuals with normal and dyslipidemic properties: a randomized controlled trial

Abstract: Objective This research was conducted as a prospective, self-controlled, eight-week clinical trial to investigate the effect of kefir consumption on the lipid profile of individuals with normal and dyslipidemic properties. Methods Kefir microorganisms given to volunteer subjects were determined using classical microbial count methods and qReal-Time Polymerase Chain Reaction. The study was carried out with 23 volunteer hospital health personnel between the ages of 20 and 55 who met the research criteria and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…However, Ghizi et al showed a decrease in serum LDL and triglycerides with kefir versus placebo in patients with metabolic syndrome, and an increase in serum high-density lipoprotein (HDL) was only observed in females [72]. Similarly, in a study including both patients with dyslipidemia and patients with normal lipid profiles, only patients with dyslipidemia displayed decreases in serum lipid concentrations, but this study did not involve a placebo group [73]. Comparable to the reported effects of kefir on immune outcomes in clinical studies, metabolic outcomes appear to be affected by host characteristics such as disease status and gender.…”
Section: Clinical Trialsmentioning
confidence: 88%
“…However, Ghizi et al showed a decrease in serum LDL and triglycerides with kefir versus placebo in patients with metabolic syndrome, and an increase in serum high-density lipoprotein (HDL) was only observed in females [72]. Similarly, in a study including both patients with dyslipidemia and patients with normal lipid profiles, only patients with dyslipidemia displayed decreases in serum lipid concentrations, but this study did not involve a placebo group [73]. Comparable to the reported effects of kefir on immune outcomes in clinical studies, metabolic outcomes appear to be affected by host characteristics such as disease status and gender.…”
Section: Clinical Trialsmentioning
confidence: 88%
“…Previous studies have indicated that the strains of Bifidobacteria and Lactobacillus have been associated with a notable reduction in serum cholesterol levels (Rubin et al., 2022 ). The regular consumption of kefir has been shown to have a positive impact on reducing total cholesterol and LDL‐cholesterol levels in blood lipid profiles, particularly in individuals experiencing dyslipidemic symptoms (Yilmaz & Arslan, 2022 ).…”
Section: Clinical Applications Of Probiotics and Prebioticsmentioning
confidence: 99%